The Application of Problem-Based Learning Strategies in Improving Learning Outcomes Students in Math Subject - Nastiti Dayana Puspa; Yantoro Yantoro; Basyir Basyir; Misnawati Misnawati (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to improve student learning outcomes in mathematics learning through the application of problem-based learning strategies. This research was conducted involving 35 students in class IV at SDN 42 / IV Jambi City. This classroom action research procedure was designed for 3 (three) cycles, where each cycle with the stages of implementation, observation, reflection and carried out with collaboration between researchers and class teachers. Based on the acquisition of learning outcomes and student and teacher observations using the application of Problem Based Learning (PBL) based learning strategies, it can be seen that the learning outcomes achieved by students have increased. This can be seen from the results in cycle I, the average student score was 63.71 in cycle II, the average student score was 68 and in cycle III the average student score reached 71.43. Likewise, the percentage of students who succeed in learning each cycle also increases, we can see in the graph above in cycle I 68.57% of students, in cycle II 77.14% of students, and cycle III 85.71% of students from the total number of students who take part in learning. So that with the application of problem-based learning strategies can improve student learning outcomes in mathematics subjects at SDN 42 / IV Jambi City.